Genetic, biological and economic evaluation of sweet potato accessions in the collection of the Plant Introduction and Acclimatization Department, Udmurt FRC, UB RAS - A. V. Fedorov; D. A. Zorin; O. A. Ardasheva (Труды по прикладной ботанике, генетике и селекции)
An important area of crop development is the introduction of new vegetable plants, one of which is the sweet potato Ipomoea batatas (L.) Lam. The aim of our research was genetic, biological and economic assessment of sweet potato accessions held in the collection of the Plant Introduction and Acclimatization Dept., Udmurt Federal Research Center, Ural Branch of the RAS (UdmFRC UB RAS).Within this experiment, DNA polymorphism of 16 accessions of I. batatas was tested using ISSR markers. All accessions were found to represent different genotypes; the VM 17 accession obtained as a result of a bud mutation differed significantly from the original accession in its genotype.Evaluation of 16 accessions of sweet potato cultivars was carried out in a small-plot field experiment. The results of biological and economic assessment witnessed to the prospects of sweet potato cultivation within the territory of the Udmurt Republic for marketable tuber production. The productivity of the accessions was 140–2700 g of tubers per plant. According to their productivity, the accessions were divided into clusters: the low-productivity group (up to 500 g), with ‘Betty’, Fioletovy, ‘Beauregard’, ‘Covington’ and Bezhevy; medium-productivity group (500–1000 g), with ‘Jewel’, Fioletovy Sochi, Brazilsky, Afgansky, Vinnitsky rozovy, Lyubitelsky and ‘Bayou Bell’; and high-productivity group (more than 1000 g), with Pobeda 100, ВM 17, Druzhkovsky and Bely NBS. On the basis of the evaluation, 11 sweet potato accessions were recommended for cultivation in the Middle Urals: Afgansky, ‘Bayou Bell’, Bely NBS, ВM 17, Brazilsky, Druzhkovsky, Fioletovy Sochi, ‘Jewel’, Lyubitelsky, Pobeda 100, and Vinnitsky rozovy.